Lipid-lowering property of Clausena anisum-olens in hypercholesterolemic rats - Anbel M. Bautista; Mario A. Tan; Jovencio M. Apostol (Taylor & Francis Group, 2017)
Context: Clausena anisum-olens (Blanco) Merr. (Rutaceae) is a medicinal shrub which has been reported to have various pharmacological uses. No study regarding the effects of C. anisum-olens on cholesterol-lowering has been reported. Objective: The effects of the ethanol extract of C. anisum-olens leaves on the cholesterol level of hypercholesterolemic rats were evaluated. Materials and methods: Acute oral toxicity of the extract (175, 550 and 2000 mg/kg) was determined using female Sprague-Dawley rats, as described in OECD 425 Main test guidelines. The lipid-lowering assay utilized 30 male Sprague-Dawley rats divided into five groups (A-E). Triton X-100 was administered to induce hypercholesterolemia. After hypercholesterolemia induction, oral treatment of Atorvastatin and crude ethanol extract was given daily to the treatment groups for 14 days. The total cholesterol, triglycerides, HDL and LDL were determined before induction, after induction, after first week of treatment and after second week of treatment. Results: Acute oral toxicity showed the crude extract is nontoxic up to 2000 mg/kg. The lipid-lowering assay indicated reduction of serum cholesterol (87.21 ± 5.10 mg/dL), triglycerides (58.09 ± 4.10 mg/dL) and LDL (27.82 ± 4.11 mg/dL) for 200 mg/kw extract. Reduction in serum cholesterol (74.72 ± 3.64 mg/dL), triglycerides (52.79 ± 2.98 mg/dL) and LDL (12.06 ± 5.51 mg/dL) were observed for 400 mg/kg group. The result is comparable to Atorvastatin, which showed serum cholesterol (80.90 ± 9.72 mg/dL), triglycerides (55.94 ± 7.19 mg/dL) and LDL (22.09 ± 7.60 mg/dL) reduction. Discussion and conclusion: The crude extract of C. anisum-olens proved to be useful in lowering of cholesterol.